Study on the utilisation of quartzite as replacement for coarse aggregate in concrete. (8th May 2019) - Shareef, Ummar; Raju, S.S.S.V. Gopala; Cheela, V.R. Sankar
Concrete is most commonly and widely used material in infrastructure development. Coarse aggregate is major ingredient of concrete which constitutes to about 60 to 70% in terms of volume of concrete. The cost of coarse aggregate is increasing day by day due to its limited availability and large demand. In the present work, Quartzite is used as an alternate material for coarse aggregate in the concrete. Experimental studies were performed on plain cement concrete by replacing coarse aggregate with quartzite up to 100%. The mix design and test methods were in accordance with the Bureau of Indian Standards. Seven and 28 day strength tests were performed on concrete cubes. The optimum percentage of quartzite replacement to coarse aggregate is found at 20%. It is observed that compressive strength increased at 20% and 100% replacement was found to be 53.2 N/mm 2 and 48.8 N/mm 2 .